Emulation of surgical fluid interactions in real-time - Stredney,Donald; Hittle,Bradley; Medina-Fetterman,Hector; Kerwin,Thomas; Wiet,Gregory (PeerJ Preprints, 2017)
The surgical skills required to successfully maintain hemostasis, the control of operative blood, requires considerable deliberate practice. Hemostasis requires the deft orchestration of bi-dexterous tool manipulation. We present our approach to computationally emulate both irrigation and bleeding associated with neurotologic surgical technique. The overall objective is to provide a visually plausible, three dimensional, real-time simulation of bleeding and irrigation in a virtual otologic simulator system. The results present a unique simulation environment for deliberate study and practice.
Keywords: Medical Simulation; Computer Graphics; Parallel Algorithms; Stereo Vision; Virtual Reality; Haptic Interfaces; Computer Aided Instruction; Data Processing; Parallel Processing